2016
DOI: 10.1007/s40123-016-0048-4
|View full text |Cite
|
Sign up to set email alerts
|

Revision External Dacryocystorhinostomy Results After a Failed Dacryocystorhinostomy Surgery

Abstract: ObjectiveTo report revision external dacryocystorhinostomy (rE-DCR) results following failed dacryocystorhinostomy (DCR) surgery.MethodsA retrospective review of patients who underwent rE-DCR between June 2006 and June 2015 at Yıldırım Beyazıt University Ankara Ataturk Training and Research Hospital Department of Ophthalmology. Data were collected on the primary surgery technique and patient demographics.ResultsForty-one rE-DCRs were performed on 40 patients after various failed DCR techniques. Two patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The aim of this study is to assess the effectiveness of early bi-canalicular silicone stenting in failed cases following DCR surgery. [3][4][5] It was found to be very effective in our study with complete resolution of symptoms following stenting.…”
Section: Introductionmentioning
confidence: 65%
“…The aim of this study is to assess the effectiveness of early bi-canalicular silicone stenting in failed cases following DCR surgery. [3][4][5] It was found to be very effective in our study with complete resolution of symptoms following stenting.…”
Section: Introductionmentioning
confidence: 65%
“…Nam Ju Kim, Were included 40 patients of failed DCR in there study and they performed dcr surgery with silicone tube intubation and concluded that Re DCR has high risk of osteotomy closure, hence this modified technique can be considered as an alternative to standard intubation technique with optimum results [11]. Emine Akcay et al (2016) were included 41 patients of failed DCR surgery in the study and concluded that the repeat external DCR procedure has high success rates for failed DCR surgeries, whichever procedure was performed [12]. Ji Sun Baek et al, (2017) were included 61 patients of failed endonasal DCR surgery and concluded that lacrimal silicone tube intubation is an effective treatment procedure for patients with functional epiphora [13].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Overall, END-DCR and EXT-DCR have a technical failure in about 10% of patients, resulting in an inefficient drainage of tears and, consequently, in relapse of watering eye (epiphora). [8][9][10] The most frequent causes of DCR failure is the presence of membranous obstruction of the nasal ostium, formation of granuloma or synechiae next to the neorhinostomy and lacrimal pump disruption. 11,12 Many treatments are available in case of recurrent epiphora after primary surgery, including observation, EXT-DCR, END-DCR and balloon dacryoplasty.…”
Section: Endoscopic Endonasal Balloondacryoplasty In Failed Dacryocystorhinostomymentioning
confidence: 99%